Assesment of Internet use in the Provision of Information to Students in University Libraries in Nigeria: A Casestudy of Afe Babalola University Library, Ekiti State, Nigeria - Oriogu, Chuks Daniel (Advances in Social Sciences Research Journal, 2015)
The Internet is a giant information super highway that plays a pivotal role in providing the information needs of users in an academic community. This study investigated the assessment of Internet use in the provision of information to students in university libraries in Nigeria: a case study of AfeBabalola university library. The study shows the capabilities of the Internet, the role of Internet in university libraries, benefits and challenges of Internet in meeting the information needs of users. The study finally makes some recommendations in combating the challenges affecting the students’ use of Internet in the university library.